AKTIVITAS ANTIRADIKAL BEBAS β-KAROTEN PADA EKSTRAK UBI JALAR (Ipomoea batatas Lamk.) DENGAN METODE DPPH (1,1-DIFENIL-2-PIKRILHIDRAZIL) IN VITRO - A.A. Hesti Wulan S; Fitri Haryanti; Nanik Wijayanti (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2011)
Sweet potato, especially orange sweet potato, contains β-carotene. The content of β-carotene in orange sweet potato is 86,46 mg/100 mg, which is more than that in the white, purple and yellow sweet potato. β-carotene has the potency as a free antiradical and anticancer. Free antiradical are compounds which have the ability to inhibit oxidation reaction and prevent free radical, so that they can protect human body from degenerative diseases like cancer, coronary heart, and diabetes mellitus. The activity of free antiradical test was conducted by DPPH (1,1-difenil-2-pikrilhidrazil) methods at the wave length of 516 nm. The sample of β-carotene extract which had been thickened, was diluted in 10.0 ml methanol. The test of free antiradical was done by adding the volume of sample 0.2 ml; 1.0 ml; 2.0 ml; 3.0 ml and 3.8 ml into DPPH solution. As comparasion, vitamin E was prepared by dissolving 0.5 g substance in 25.0 ml methanol. Then, series of concentration 0.01%; 0.02%; 0.04%; 0.06% and 0.08% was made. The activity was measured in the percentage of muting free radical DPPH in thirty minutes. The data of the determination result of β-carotene free antiradical was evaluated its value of EC20 and compared to the value of EC20 in vitamin E. Based on the result, the research shows that the value of EC20 β-carotene in sweet potato extract is 402.4343 μg/ml, while that in vitamin E is 2.6299 μg/ml. Therefore, it can be concluded that β-carotene in sweet potato extract has lower activity of free antiradical than in vitamin E.